Epidemiological Insights into Erysiphe polygoni-Induced Powdery Mildew of Blackgram under In-vitro Conditions - , V. Vasanthi; , P. Kishore Varma; , M. Suresh; , N. Kamakshi; , Ch. Rani; , D. Ramesh; , J. Vasanthi; , B. Pushparajyam (Archives of Current Research International, 2025)
Aim: Powdery mildew, incited by Erysiphe polygoni D.C, is a prominent foliar disease of blackgram (Vigna mungo L.) that adversely impacts all developmental stages, culminating in premature defoliation and yield losses reaching up to 70%. The disease initiates as subtle, white powdery flecks on the abaxial surface of lower leaves subsequently proliferating into dense mycelial colonies that envelop aerial plant parts, persisting until physiological maturity. Despite its economic significance, the epidemiology of this pathogen under varying environmental conditions remains inadequately explored. The present investigation aimed to dissect the influence of environmental factors on conidial germination of E. polygoni under controlled in vitro conditions. Methodology: A spectrum of carbon sources, temperature regimes and relative humidity (RH) levels were evaluated under invitro conditions at RARS, Lam, Guntur during December, 2024. Results: Among carbon substrates, 2.0% dextrose demonstrated the highest conidial germination rate (77.33%), markedly surpassing other treatments. This was trailed by glucose (72.67% at 1.5%) and sucrose (72.00% at 1.5% and 70.67% at 2.0%) whereas sterile water yielded the lowest germination (51.33%). Temperature analysis revealed optimal germination (64.67%) at 24°C with significant inhibition at lower extremes—15°C (37.67%) and 18°C (40.67%). Humidity trials underscored 80% RH as the most conducive, achieving 78.33% germination whereas 50% RH exhibited a suppressive effect with germination plummeting to 36.33%. Conclusion: This study underscores the intricate interplay of environmental parameters in regulating the infective potential of E. polygoni.